IF YOU WANT TO BE A CEO, LEARN TO BE AGILE - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
Before you dart off to the nearest gym, look for the monkey bars or stretching on the exercise mat, this is not about training yourself to become the next bona fide guy with spider-like agilities. This is about the agility of the mind. A person having a high agility to learn would be capable of learning at a faster and more flexible pace.